KONTRIBUSI BIMWINCATIN DALAM PEMAHAMAN PENGELOLAAN KEUANGAN RUMAH TANGGA DI KUA KEC. BAROS - Dzikra Qatrunnada; Najwa Auliya; Reva Amelia Hasanah Samin; Hunainah (STKIP Subang, 2026)
The Pre-Marital Guidance Program for Prospective Brides and Grooms (Bimwincatin) at the Office of Religious Affairs (KUA) of Baros District plays an important role in improving prospective couples’ understanding of household financial management. Household financial management is an essential aspect of family life because it is related to the ability of husband and wife to manage income, distinguish primary and secondary needs, conduct deliberation in the use of money, save, and plan family finances. This study uses a descriptive qualitative approach with an interview method. Data were obtained through interviews with the KUA Baros District officer, namely a marriage registrar who is involved in the implementation of the Bimwincatin program. The research instrument was developed based on indicators of understanding household financial management, including the concept of sustenance, family needs priorities, financial openness between husband and wife, deliberation in using family income, saving, emergency funds, and investment. In addition, this study is supported by literature reviews and documentation related to the Bimwincatin program. The results of this study are expected to provide an overview of the implementation of the Bimwincatin program at KUA Baros District and to show the contribution of the program in preparing prospective married couples to manage household finances properly. This study is expected to serve as an evaluation and development reference for improving the Bimwincatin program as an effort to enhance the quality of family life in society.